Analysis of Genetic Variability Amongst Polyploid Genotypes of Pteris vittata L. From Various Geographic Locales of India - Mathur, Jyoti; Khare, P. B.; Panwar, Apurva; Ranade, S. A. (Frontiers in Ecology and Evolution, 2021)
Pteris vittata L. is very common and a widely distributed species belongs to the family Pteridaceae. Various cytotypes from diploid to octaploid is available in this fern species. The present work has been carried out for genetic diversity in this fern both within and between the cytotypes. The molecular analysis at inter- as well as intra-species has been carried out with 57 accessions of P. vittata as well as of other species of Pteris with Microsorium punctatum considered as an out group taxon. For the present study 48 P. vittata (36 tetraploid and 12 pentaploid) and five of other species (four P. cretica, one P. pellucida, one P. tremula, one P. quadriaurita and two P. ensiformis) accessions were used. The UPGMA (unweighted pair group method with arithmetic mean) dendrograms were generated for each method separately, as well as for all methods cumulatively, after a 1000 replicate bootstrap analysis. In order to determine the utility of each of the method, a comparative statistical assessment was done and marker index (MI), expected average heterozygosity, fraction of polymorphic loci and effective multiplex ratio (EMR) were calculated in case of each of the methods used in the present study. At the level of individual methods highest MI was obtained for directed amplification of minisatellites DNA (DAMD) method. Our findings of the present study concluded that out of the three methods Random Amplified Polymorphic DNA (RAPD), Inter-Simple Sequence Repeat (ISSR), and Directed Amplification of Minisatellite DNA (DAMD), DAMD was the best in term of polymorphism and heterozygosity as scores exhibited highest MI. The different accessions of P. vittata collected from different phytogeographical regions falls into six groups. Out of six clusters, one cluster is of pentaploid cytotype, four clusters are of tetraploid cytotype and one for outgroup taxon (Microsorium punctatum). The result thus showed that within tetraploid, heterozygosity with variable genomic structure exists.